2009
DOI: 10.1016/j.ccr.2009.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Raf-1 Addiction in Ras-Induced Skin Carcinogenesis

Abstract: Ras activation is common to many human cancers and promotes cell proliferation and survival by initiating multiple signaling cascades. Accordingly, Ras-transformed cells are generally considered too resourceful to become addicted to a single effector. In contrast to this tenet, we now demonstrate an absolute, cell autonomous requirement for Raf-1 in the development and maintenance of Ras-induced skin epidermis tumors. Mechanistically, Raf-1 functions as an endogenous inhibitor dimming the activity of the Rho-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
111
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(126 citation statements)
references
References 54 publications
(77 reference statements)
13
111
1
1
Order By: Relevance
“…Recently, we have shown that endogenous C-Raf is essential to maintain an undifferentiated status in Ras-driven epidermal tumors. Conditional ablation of C-Raf results in rapid regression of established tumors through MEK/ERK-independent activation of a differentiation program induced by hyper-activation of the cytoskeleton-based kinase Rok-a (Ehrenreiter et al, 2009). These data show that Ras-driven tumors are addicted to non-oncogenic C-Raf, and offer proof of principle that differentiation (co)therapy may be feasible in solid tumors.…”
Section: Raf and The Hallmarks Of Cancermentioning
confidence: 64%
See 1 more Smart Citation
“…Recently, we have shown that endogenous C-Raf is essential to maintain an undifferentiated status in Ras-driven epidermal tumors. Conditional ablation of C-Raf results in rapid regression of established tumors through MEK/ERK-independent activation of a differentiation program induced by hyper-activation of the cytoskeleton-based kinase Rok-a (Ehrenreiter et al, 2009). These data show that Ras-driven tumors are addicted to non-oncogenic C-Raf, and offer proof of principle that differentiation (co)therapy may be feasible in solid tumors.…”
Section: Raf and The Hallmarks Of Cancermentioning
confidence: 64%
“…In the case of C-Raf, other targets potentially contributing to cell transformation have been proposed, such as the nuclear factor-kB pathway (Baumann et al, 2000), Rb (Kinkade et al, 2008) and BAD (Polzien et al, 2009), all reviewed by Niault and Baccarini (2010). In addition, C-Raf can inhibit apoptosis by binding to, and inhibiting, the stress-induced kinase ASK-1 (Chen et al, 2001) and the homolog of Drosophila's Hippo, the MST-2 kinase (O'Neill et al, 2004;Matallanas et al, 2007); and finally, C-Raf interferes, by direct binding, with the activity of the cytoskeleton-based Rho effector Rok-a (also known as ROCK2), resulting in defects in cell migration, apoptosis and differentiation (Ehrenreiter et al, 2005(Ehrenreiter et al, , 2009Piazzolla et al, 2005) (Figure 2). …”
mentioning
confidence: 99%
“…Mouse strains and genotyping have been previously described (14). Strains were maintained on a 129Sv/Bl6 (F1) background.…”
Section: Mouse Strains and Inhibitor Treatmentmentioning
confidence: 99%
“…This situation is parallel to the situation in cancers which are addicted to activities of factors such as myc and Raf [8][9][10], and loss or diminishing the function of these factors causes the tumor cells to grow at a diminished pace. Myelan et al use nuclear accumulation of p65 as a measure of NFκB activation in this study.…”
mentioning
confidence: 88%